Purchaser-supplier relationship in third party procurement : a case study in Chinese automotive industry : a thesis presented fulfillment of the requirements for the degree of Master in Logistics and Supply Chain Management at Massey University, Palmerston North, New Zealand - Liu, Luying (Massey University, 2015)
The purpose of the research is to evaluate the role of third party procurement (3PP) in supply chain. The relationship between third party purchasers and suppliers will be explored and some suggestions will be proposed to improve the relationship. The research will focus on Chinese automotive industry, so a typical third party procurement provider in this industry will be analyzed as a case study. Data will be collected mainly through interviews among the third party purchasers and their suppliers, and the data will be analyzed and interpreted in a qualitative method. Studies have shown that outsourcing is getting more and more popular. 3PP is inevitably involved when it comes to procurement outsourcing. Due to the professional services from the third party procurement providers, not only the supply chain efficiency can be improved, but also the client firms can gain benefits from the value they create. However, 3PP also has disadvantages. It is necessary for enterprises to identify these pros and cons before outsourcing procurement. In addition, the relationship between third party purchasers and suppliers should also be paid attention. In this research, this kind of relationship will be explored and put forward some suggestions to improve the relationship and increase satisfaction of both sides.
Keywords: Industrial procurement; Business logistics; Automobile industry and trade; China